2021
DOI: 10.3390/jcm10184051
|View full text |Cite
|
Sign up to set email alerts
|

Collagen XII Deficiency Increases the Risk of Anterior Cruciate Ligament Injury in Mice

Abstract: Anterior cruciate ligament (ACL) rupture is a common knee injury for athletes. Although surgical reconstruction is recommended for the treatment of ACL ruptures, 100% functional recovery is unlikely. Therefore, the discovery of risk factors for ACL ruptures may prevent injury. Several studies have reported an association between polymorphisms of the collagen XII gene COL12A1 and ACL rupture. Collagen XII is highly expressed in tendons and ligaments and regulates tissue structure and mechanical property. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As with osteoblasts, the altered tenocyte shape, and impaired cell-cell connection/communication via connexin 43 found in Col12a1 null mice may be due to the lack of collagen XII bridge formation between cells. This alteration is associated with less compartmentalized as well as disorganized tendon structure, altered tendon mechanical properties (Izu et al, 2021;Fung et al, 2022), and increased risk of articular cruciate ligament injury (Fukusato et al, 2021). These data indicate the essential role of collagen XII bridge formation during tenocyte network formation and coordination of the tendon hierarchical structure and mechanical properties.…”
Section: Collagen XII Regulates Cell-cell Communication Via Collagen ...mentioning
confidence: 79%
See 1 more Smart Citation
“…As with osteoblasts, the altered tenocyte shape, and impaired cell-cell connection/communication via connexin 43 found in Col12a1 null mice may be due to the lack of collagen XII bridge formation between cells. This alteration is associated with less compartmentalized as well as disorganized tendon structure, altered tendon mechanical properties (Izu et al, 2021;Fung et al, 2022), and increased risk of articular cruciate ligament injury (Fukusato et al, 2021). These data indicate the essential role of collagen XII bridge formation during tenocyte network formation and coordination of the tendon hierarchical structure and mechanical properties.…”
Section: Collagen XII Regulates Cell-cell Communication Via Collagen ...mentioning
confidence: 79%
“…The generation of genetically modified Col12a1 animals has allowed further definition of the functions of collagen XII (Izu et al, 2011;Agarwal et al, 2012;Hemmavanh et al, 2013;Marro et al, 2016;Wehner et al, 2017;Schönborn et al, 2020;Sun et al, 2020;Fukusato et al, 2021;Izu et al, 2021;Fung et al, 2022). A mouse Collagen XII interacts with the collagen I-containing fibril surface via its collagenous domain.…”
Section: Col12a1 Mutations In Human Diseasesmentioning
confidence: 99%
“…In mouse flexor digitorum longus tendons, Collagen XII, which is a mechanosensitive molecule, expresses throughout the tendon with no difference in distribution with age 36 . Col12a1-/-mice displayed discontinuities in 20%-60% of the ACL, suggesting that Col12a1 regulates ligament structure and mechanical properties 37 . Collagen XIV is expressed in areas of high mechanical stress, such as skin, tendon, and cartilage 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed morphological analysis of different tendons revealed that 20–60% of the KO mice display discontinuity in the anterior, but not in the posterior cruciate ligament and have an increased risk of anterior cruciate ligament injury. 10 These studies show that collagen XII is crucial for ECM integrity in bone and tendon but the consequences for joint stability and function are poorly understood.…”
Section: Introductionmentioning
confidence: 99%